Α Tool for Litigation Risk Analysis for Medical Liability Cases - Vozikis, Athanassios; Panagiotou, Athanasios; Karakolias, Stefanos (HAPSc Policy Briefs Series, 2021)
Mistakes in the context of medical care can occur anywhere in the healthcare system. On the one hand, the doctrinal uncertainties, which lie at the heart of the current medical liability system, combined with the inherent uncertainty of medical science and the human body’s complexity, create an extremely “foggy” landscape. On the other hand, litigation is not always effective. Thus, it is essential to cope with the uncertainties in a reasoned way. This paper presents a tool for litigation risk analysis in medical liability cases which permits identification of the multiple uncertainties that will affect the potential outcome and the exploration of their interrelationships. The basic uses, purposes and features of the tool will be presented. In addition, its core advantages as well as and its aims, benefits and financial/social/scientific impact will be discussed.